The Nurse as a Member Responsible for Implementing the Community Health Politics - Bēta, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The nurse is a medical practitioner, who performs not only the practical skills of her/his chosen profession. She/he is also an important member of the chain, responsible for the community education work. The education process occurs during the daily planned or unplanned communication with patients of different age or with family members and visitors. The nurse is often asked for an advice, not rarely she is the trustee of the patient because her actual role is well understandable to the patients, she/he is relatively closer. Nevertheless, not always the expectations of visitors of health care establishments, patients or members of their families to get valuable information from the nurse in the context of a specific situation have been satisfied. Considering health strategy of EU and Latvia the nurses have to be aware of the ongoing and prospective importance of educational work. Besides to knowledge of the professional spectrum the scope of educational methods applicable in the education of patients is of great importance: appropriate usage of these methods may encourage the patient’s comprehension of the current situation or of the total educational process. Correctly chosen educational methods and communication approach may have a positive influence on patients’ life quality and, secondarily, encourage the implementation of community health politics.